Respostas

  • Usuário do Brainly
2013-02-18T22:03:34-03:00

Temos que:

 

\text{X}=\left(1+\text{a}^{\frac{1}{3}}\right)\left(1-\text{a}^{\frac{1}{3}}+\text{a}^{\frac{2}{3}}\right)

 

Observe que:

 

\text{a}^{\frac{1}{3}}=\sqrt[3]{\text{a}}

 

\text{a}^{\frac{2}{3}}=\sqrt[3]{\text{a}^2}

 

Desta maneira, temos:

 

\text{X}=(1+\sqrt[3]{\text{a}})(1-\sqrt[3]{\text{a}}+\sqrt[3]{\text{a}^2})

 

\text{X}=1+\sqrt[3]{\text{a}}+\sqrt[3]{\text{a}^2}+\sqrt[3]{\text{a}}-(\sqrt[3]{\text{a}})^2+\sqrt[3]{\text{a}^3}

 

Donde, obtemos:

 

\text{X}=1+\text{a}